Physical Characteristics and Technology of Glass Foam from Waste Cathode Ray Tube Glass. (20th March 2013) - Mucsi, G.; Csőke, B.; Kertész, M.; Hoffmann, L.
Abstract : This paper deals with the laboratory investigation of cathode-ray-tube- (CRT-) glass-based glass foam, the so-called "Geofil-Bubbles" which can be applied in many fields, mainly in the construction industry (lightweight concrete aggregate, thermal and sound insulation, etc.). In this study, the main process engineering material properties of raw materials, such as particle size distribution, moisture content, density, and specific surface area, are shown. Then, the preparation of raw cathode ray tube glass waste is presented including the following steps: crushing, grinding, mixing, heat curing, coating, and sintering. Experiments were carried out to optimize process circumstances. Effects of sintering conditions—such as temperature, residence time, and particle size fraction of green pellet—on the mechanical stability and particle density of glass foam particles were investigated. The mechanical stability (abrasion resistance) was tested by abrasion test in a Deval drum. Furthermore, the cell structure was examined with optical microscopy and SEM. We found that it was possible to produce foam glass (with proper mechanical stability and particle density) from CRT glass. The material characteristics of the final product strongly depend on the sintering conditions. Optimum conditions were determined: particle size fraction was found to be 4–6 mm, temperature 800°C, and residence time 7.5 min.